2011
DOI: 10.4414/smw.2011.13270
|View full text |Cite
|
Sign up to set email alerts
|

The use of copeptin, the stable peptide of the vasopressin precursor, in the differential diagnosis of sodium imbalance in patients with acute diseases

Abstract: Although limited by small sample size, this study found that plasma copeptin level appears to add very little information to the work up of sodium imbalance in this cohort of medical inpatients. It is likely that the non-osmotic "stress"-stimulus in acute hospitalised patients is a major confounder and overrules the osmotic stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…These data indicate that GFR, as such, is not a determinant of copeptin levels. In the literature, the association between kidney function and plasma copeptin has been described in several studies, with higher copeptin concentrations when kidney function is lower (15)(16)(17)(18). In our opinion, two mechanisms can underlie the negative association in these studies.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These data indicate that GFR, as such, is not a determinant of copeptin levels. In the literature, the association between kidney function and plasma copeptin has been described in several studies, with higher copeptin concentrations when kidney function is lower (15)(16)(17)(18). In our opinion, two mechanisms can underlie the negative association in these studies.…”
Section: Discussionmentioning
confidence: 74%
“…Copeptin has a molecular mass of only 5 kD, which makes it subject to kidney clearance. Indeed, several studies showed inverse associations between kidney function and copeptin (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…ADH assay, while helpful to differentiate between the two, is often inaccurate due to ADH's instability in the blood. Radioimmunoassays which detect copeptin, a stable molecule secreted with ADH may be helpful in quantification of serum ADH levels [113,115].…”
Section: Differential Diagnosis Of Diabetes Insipidusmentioning
confidence: 99%
“…SIADH) from hypovolemic hyponatremia [76]. It is also worth mentioning that higher copeptin concentration is observed in patients with hyponatremia in course of chronic renal failure compared to patients with gastrointestinal loss [77].…”
Section: Copeptin In Hyponatremia and Diabetes Insipidusmentioning
confidence: 99%